The Integration of Duolingo in Classroom Setting: A Case Study of its Impact on English Language Learning. - Azhima, Fauzan; Halim*, Abdul (Universitas Syiah Kuala, 2024)
The rising role of technology in education has caused a renewed interest in studying interactive educational systems. This study focuses into the usage of the Duolingo platform as an interactive learning tool, assessing its potential impact on language acquisition and engagement among users. The purpose of this study is to evaluate Duolingos performance as an interactive learning tool for language learning. This study integrates a case study approach with descriptive quantitative methods. Several instruments are used, such as questionnaires, activity records, and interviewing. Surveys and student activity logs provide quantitative insights into learning outcomes and engagement among users are analyzed. Moreover, qualitative data gathered from interviews is examined using a thematic approach to better understand user experiences and perspectives. The result of this study shows that Duolingo's integration into traditional educational settings significantly improves participants' motivation and attitudes toward language learning. for about 94.7% feeling more motivated as a result of its engaging elements such as scores, hearts, rankings, and rewards. Duolingo also improving proficiency in listening, speaking, vocabulary, and grammar through personalized and repetitive tasks.